2016
DOI: 10.1111/1556-4029.13031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self‐Injurious Behaviors and Levels of Aggression in Children and Adolescents Who Were Subject to Medicolegal Examination,

Abstract: Aggression, which is defined as a behavior causing harm or pain, is a behavioral pattern typically expected in children and adolescents who are involved in criminal activities. The aim of this study was to examine the relationship between aggression and self-injurious behavior (SIB) in children and adolescents. The study was performed in 295 cases which were sent for medicolegal examination. The mean age of the subjects was 14.27 ± 1.05 years (age range 10-18 years). The aggression levels of the subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
2
1
2
Order By: Relevance
“…In the literature, although some studies reported that there was no significant difference between the sexes in terms of NSSIB incidence (5,19,(38)(39)(40)(41)(42), some other studies reported that the incidence of NSSIB was higher in females (9,10,37,43). In our study, no statistically significant difference was found in sex distribution between the NSSIB (+) and NSSIB (-) groups.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In the literature, although some studies reported that there was no significant difference between the sexes in terms of NSSIB incidence (5,19,(38)(39)(40)(41)(42), some other studies reported that the incidence of NSSIB was higher in females (9,10,37,43). In our study, no statistically significant difference was found in sex distribution between the NSSIB (+) and NSSIB (-) groups.…”
Section: Discussioncontrasting
confidence: 70%
“…Nonsuicidal self-injurious behavior (NSSIB) is defined as intentional harm to one's body without intentions of committing suicide (3)(4)(5)(6). The most common methods are self-cutting (70%-97%), self-hitting (21%-44%), selfburning (15%-35%), and severe scratching (4%-13%) Apart from direct methods such as self-biting, scratching, tissue plucking, burning, hitting, and compressing, there are also indirect NSSIB methods including overeating, undereating, substance use, and rejection of medical treatment (5,7,8). In some studies, it was noted that more than half of NSSIB cases involved more than one method (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros sete trabalhos recrutaram as amostras em locais diversos 9,20,35,37,40,65,68 . De um modo geral, a concentração de estudos em escolas era esperada, uma 34,[36][37][38][39][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]62,63,[65][66][67][68][69]72,73,[74][75][76][77][78][79] , havendo oito que incluíram apenas adolescentes do sexo feminino 9,10,33,35,…”
Section: Caracterização Da Amostraunclassified
“…Em relação ao delineamento metodológico, a maioria dos estudos apresentam métodos de natureza quantitativa 9-19,21-36,38-57,59-75,77-79 (67 artigos), sendo apenas dois artigos caracterizados como qualitativos 20,58 e 2 apresentando métodos mistos (quali-quantitativo) 37,76 . Dentre os estudos quantitativos, 56 apresentam delineamento transversal [9][10][11][12][14][15][16][17][18][19]21,22,[24][25][26]29,[32][33][34][35][36][38][39][40][41][42][44][45][46][47][48][49][51][52][53][54]56,[59][60][61][62][63][64][65][66][68][69]…”
Section: Caracterização Da Amostraunclassified